Monitoramento de ativos de rede utilizando softwares open-source - Medrado, Rainer Testa (2018)
This paper presents a practical case study on the use of monitoring solutions in a datacenter environment. Essential concepts are presented on the SNMP protocol, which was developed to facilitate the monitoring and management of networks. Also presented are Zabbix and Cacti software, with its PHP Network Weathermap plugin, where all procedures performed will be documented, from installation to configuration of the monitoring service, configuration of maps and use of templates and development of link use map of the data, all according to the official documentation of the software.